Research on the Reconstruction of the Innovative Talent Training Model of "Three Chain Synergy" in Design Specialty with AIGC Empowerment from the Perspective of Industry-Education Integration - Jiang, Yude (Education Insights, 2026)
Industry-education integration serves as the cornerstone for higher education to align with industrial demands and cultivate applied innovative talents in the new era. The iterative application of AIGC technology has injected digital momentum into the deep synergy of the education chain, talent chain, and industrial chain in design disciplines. However, current "three-chain synergy" training in design programs faces challenges such as superficial integration, insufficient AIGC empowerment, and disconnection between talent cultivation and industrial digitalization needs, making it difficult to meet the requirements of intelligent transformation in the design industry. This paper examines industry-education integration through the lens of AIGC technology’s core empowering value, defining the essence of AIGC-driven "three-chain synergy" in design education. It analyzes existing limitations in talent cultivation models and explores an innovative framework: "industry-education integration as the foundation, AIGC technology as the driver, and three-chain synergy as the goal." Practical pathways and safeguard strategies for model reconstruction are proposed, aiming to provide theoretical references and practical paradigms for design disciplines to deepen industry-education integration, achieve "three-chain" synergy, and cultivate innovative design talents aligned with industrial development through AIGC technology.